Implementing Minimum Education Service Standards to Enhance Learning Quality in Indonesian Junior High Schools - Fitri Setiawati; Ismail Ismail; Niswanto Niswanto; Kamaluddin Kamaluddin; Aida Warni (MASI Mandiri Edukasi, 2025)
This study investigates the implementation of Minimum Service Standards (SPM) in Education at SMP Negeri 4 Trumon Timur, South Aceh Regency, to evaluate its effectiveness in improving learning quality at the junior high school level. Employing a descriptive qualitative approach through interviews, observations, and documentation studies, the research analyzes learning planning, implementation processes, and infrastructure support using the Miles and Huberman interactive model. The results show that learning plans align with curriculum standards and basic competencies, teaching practices meet media and competency requirements, and infrastructure, such as laboratories, libraries, and technology facilities, adequately support learning activities. The implementation of SPM effectively enhances educational quality and supports the national goal of creating intelligent, character-driven learners. The findings provide valuable guidance for local governments and education authorities in formulating equitable and sustainable education policies to strengthen the realization of minimum service standards across regions.